Numerical simulation of droplet coalescence behavior in gas phase under the coupling of electric field and flow field. Issue 3 (4th March 2018) - Hong, Wenpeng; Ye, Xiangyun; Chen, Qicheng
ABSTRACT: The coalescence behavior of droplets in an electric field belongs to the important research contents of electrohydrodynamics. Based on the phase field method of the Cahn–Hilliard equation, the electric field and the flow field are coupled to establish the numerical model of twin droplet coalescence in a coupled field. The effects of flow rate, electric field strength, droplet diameter, and interfacial tension on the coalescence behavior of droplets during the coalescence process were investigated. The results show that the dynamic behavior of the droplets is divided into coalescence, after coalescence rupture, and no coalescence under the coupling of electric field and flow field. The proper increase of the electric field strength will accelerate the coalescence of the droplets, and the high electric field strength causes the droplets to burst after coalescence. Excessive flow rates make droplets less prone to coalescence. Under the coupling field, the larger the droplet interface tension, the smaller the droplet diameter, the smaller the flow rate, and the shorter the droplet coalescence time. The results provide a theoretical basis for the application of electrostatic coalescence in gas–liquid separation technology. GRAPHICAL ABSTRACT: